Allergic rhinitis behavioral changes after Indonesian house dust mites allergenic extract administration as immunotherapy - Yusuf A. Pratama; Honey D. Marhaeny; Lutfiatur Rohmah; Salsabilla M. Kasatu; Ahmad D. Nurhan; Mahardian Rahmadi; Junaidi Khotib (Journal of Public Health in Africa, 2023)
Background: Allergy is a hypersensitivity reaction that is generally mediated by Immunoglobulin E (IgE). More than 25% of the world’s population is suspected of having these various diseases, and the prevalence and progression of these diseases have continued to increase significantly in recent years. Among these allergy-related diseases, allergic rhinitis and food allergy are the types of allergies with the highest prevalence. Clinical manifestations of allergic rhinitis include sneezing, rhinorrhea, nasal itching, and nasal congestion. Objective: This study aimed to determine the behavioral changes of allergic rhinitis after Indonesian House Dust Mites (IHDM) allergenic extract administration as an immunotherapy. Methods: Eight male BALB/c mice aged 6-8 weeks in each group were treated for seven groups. The sensitization phase is given intraperitoneal, the desensitization phase is given by subcutaneous, and the challenge phase is given intranasal. The allergic parameters were observed, such as nose rubbing and sneezing. The parameters were observed for 15 minutes after the challenge administration. Results: The results showed that the administration of Indonesian House Dust Mites as immunotherapy decreased the frequency of nose rubbing and sneezing after the administration of immunotherapy compared to the allergic rhinitis model. Conclusions: The administration of the Indonesia House Dust Mites as immunotherapy decreased the allergic rhinitis immune response by altering the behavioral parameter.